Kebijakan pelayanan kesehatan reproduksi bagi perempuan penyandang disabilitas dalam rangka pencegahan kekerasan seksual - Tri Joko Sri Haryono; Toetik Koesbardiati; Siti Mas'udah (Faculty of Social and Political Science, Universitas Airlangga, 2015)
The issue of women with disabilities is still rarely studied and published in the community, especially the issues of sexual violences for women with disabilities. This study provides a recommendation for both central and local governments (especially in East Java) to accomodate reproductive health services for women with disabilities. Since The Convention on the rights of persons with disabilities through the Law no.19 in 2011, the government have not taken any significant action. Therefore, it is necessary to establish a more implementative model policy for the community. The purpose of this research acts as a reference to make an effective, efficient, and right-on-target reproductive health policy. The recommendation made in this study is expected to be a reference for various parties, including the government, in order to design a more concrete and proactive steps to overcome reproductive health issue for women with disabilities in Indonesia, and also to build strategies which unite communities with different backgrounds. In order to obtain empirical data and information, this study used descriptive research with qualitative approach. Several steps taken are (1) determining the location of the study purposively in 33 sub-districts of Malang regency: in clinic, health, education, and social department, boarding school, Bhakti Luhur, P2TP2A, and local NGOs. Malang regency is chosen because (a) it is the only city which starts concerning sexuality and reproductive health of women with disabilities issues; (b) The sex ratio in 2010 was around 98,78%, which means that the number of females is significantly larger than males. As seen from the population density of 33 sub-districts of Malang, the majority of women has high density above 2000/km². It implies that poverty is mostly suffered by women; (c) the number of reproductive health issues for women with disabilities is quite a lot, because it is regarded as a taboo. (2) Data Collection: (1) observation and (2) indepth interview, (3) informants, (4) data analysis. The result of this study indicates that there are still a lot of women with disabilities who do not understand about taking care of their reproductive organs, and thus impacting their health. The control over their reproductive organs is still low, which makes many of them suffered from sexual violences that lead to unwanted pregnancies. Some cases found during the study show that women with disabilities who become sexual violence victims did not get proper justice, because their statements are not legally accepted, and it is also reinforced by the communities’ stigma which calls person with mental disabilities as a psycho.